Sistem Informasi Penjadwalan Mata Pelajaran Berbasis Web Menggunakan Metode Prototyping Pada SMKN 9 Medan - Muhammad Zen; Rahmad Budi Utomo; Nurul Hamdi (STMIK Budi Darma, 2023)
SMK Negeri 9 Medan is a Vocational High School located in Medan City with various majors, such as Social Nursing, Computer Network Engineering, Software Engineering, Multimedia, Animation, and Visual Communication Design. Scheduling subjects is necessary so that the teaching and learning process can take place. The process of scheduling conventional subjects often results in schedule collisions. To overcome these problems the authors conducted research aimed at creating a Web-based Subject Scheduling Information System using the Prototyping Method. This application was created to prevent schedule collisions and facilitate the process of making subject scheduling. The prototyping method is carried out by interviewing prospective users. The resulting system helps with scheduling with a class schedule approach in one week. So that making a schedule only needs to choose subjects and supporting teachers. In addition, users are assisted by the set number of schedules below the minimum and standards for consideration in making schedules.